Effect of double doping of CUO films with cadmium and cobalt eras on the structural and electrical properties - Nabeel khalil Husien; J. Alzanganawee (Genius Journals, 2022)
In this study, CuO thin films were deposited from the preparation of a gelatinous solution of aqueous copper acetate at a concentration of 0.6 M dissolved in 2-methoxyethanol, and mono ethanolamine was added to neutralize the pH of the solution to reach (Ph =7)) onglass bases and double-grafted with cadmium and cobalt in equal proportions
Keywords: aqueous copper acetate; cadmium acetate; cobalt acetate; sol-gel method